2021
DOI: 10.3390/agriculture11060512
|View full text |Cite
|
Sign up to set email alerts
|

Aroma Profile, Microbial and Chemical Quality of Ensiled Green Forages Mixtures of Winter Cereals and Italian Ryegrass

Abstract: The objective of this study was to evaluate the aroma profile, microbial and chemical quality of winter cereals (triticale, oats, barley and wheat) and Italian ryegrass (Lolium multiflorum Lam., IRG) plus winter cereal mixture silages detected with an electronic nose. Four commercial mixtures (mixture A (40% of two cultivars of winter triticale + 30% of two cultivars of winter oats + 20% of winter barley + 10% of winter wheat), mixture B (50% of two cultivars of winter triticale + 40% of winter barley + 10% of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 28 publications
2
8
0
Order By: Relevance
“…This can be related to the stage of maturity and chemical composition of the plants at this phase of growth. The third cut in Mixtures A and B was closer to a less mature stage, while in Mixtures C and D, the third cut was closer to a more mature stage as observed by Worku, Tóth, et al (2021) in an earlier study involving the nutritional composition of these forage mixtures at different phenological phases (Table 1). Cut 3 represented the stage where the samples containing Italian ryegrass separated the most from those containing winter cereals only as also demonstrated by Figure 2b showing the same PCA scores colored by the four different mixtures.…”
Section: Resultssupporting
confidence: 74%
See 4 more Smart Citations
“…This can be related to the stage of maturity and chemical composition of the plants at this phase of growth. The third cut in Mixtures A and B was closer to a less mature stage, while in Mixtures C and D, the third cut was closer to a more mature stage as observed by Worku, Tóth, et al (2021) in an earlier study involving the nutritional composition of these forage mixtures at different phenological phases (Table 1). Cut 3 represented the stage where the samples containing Italian ryegrass separated the most from those containing winter cereals only as also demonstrated by Figure 2b showing the same PCA scores colored by the four different mixtures.…”
Section: Resultssupporting
confidence: 74%
“…From the loading plots (b,d), it could be observed that sugar content (CH bonds, at 2350 nm) (Workman & Weyer, 2012) was the most prominent component causing the difference between the two clusters, not including and including Italian ryegrass (Mixtures A and B and Mixtures C and D, respectively). As confirmed by the chemical analysis, Mixture B had significantly lower CF and NDF content on Day 90, compared with Mixtures A, C, and D (Worku, Tóth, et al, 2021).…”
Section: Resultsmentioning
confidence: 75%
See 3 more Smart Citations